Commercial fishing gear modifications to reduce interactions between Atlantic sturgeon (Acipenser oxyrinchus oxyrinchus) and the southern flounder (Paralichthys lethostigma) fishery in North Carolina (USA) - Levesque,Juan C.; Hager,Christian; Diaddorio,Eric; Dickey,R. Jason (PeerJ, 2016)
Bycatch of protected species in commercial fishing operations is a primary concern to fishery managers because it threatens the conservation, protection, and recovery of fragile species, such as the Atlantic sturgeon (Acipenser oxyrinchus oxyrinchus). One potential solution to reduce the risk associated with commercial fishing operations is to design commercial fishing gear that is more selective in terms of interactions between Atlantic sturgeon and commercial fisheries. Given this conservation and management need, the overarching goal was to reduce Atlantic sturgeon fishery interactions and maintain southern flounder (Paralichthys lethostigma) catch in North Carolina. The specific objectives of this study were to design and evaluate the effectiveness of a modified gillnet. Overall, the results proved that lowering the profile and amount of webbing had a beneficial impact at reducing Atlantic sturgeon incidental encounters and bycatch. The modified gillnet reduced bycatch and Atlantic sturgeon encounters by 39.6% and 60.9%, respectively. Our design entangled 51.6% fewer southern flounder, which corresponded to a 48.9% reduction in total weight; the modified gear entangled slightly larger southern flounder than the control gear. Our findings showed the number of Atlantic sturgeon encounters was positively associated with mean water depth, with more Atlantic sturgeon encountered in deeper (5.1–6.3 m) than shallower waters; 75% were encountered at depths between 4.6 and 6.1 m. Most southern flounder (n = 518, 39.7%) were taken at a water depth between 3.76 and 5.0 m. This observation suggests that southern flounder prefer slightly shallower waters than Atlantic sturgeon.
Keywords: Bycatch; Commercial fisheries; Fishery interactions; Protected species